FEATURES OF THE IMPLEMENTATION OF THE LEGAL MECHANISM OF PUBLIC ADMINISTRATION IN THE FIELD OF PROVISION OF SERVICES TO INTERNALLY DISPLACED PERSONS - Moroz, S. (Public administration and state security aspects, 2025)
The current state of implementation of the legal mechanism of public administration in the field of providing services to internally displaced persons in Ukraine is analyzed. The problems of providing services to internally displaced persons are identified, as well as ways to solve problematic issues in this area by improving financial and organizational and legal support.